Banyol in Panakawan Wayang Golek Style Karawang - Asep Wadi; Anggy Giri Prawiyogi (LPPM Universitas Buana Perjungan Karawang, 2021)
Banyol panakawan is a form of sempal kapiguyon, because in essence the meaning of sempal kapiguyon is to entertain the figures of the knights or ponggawa among them. Because a panakawan figure is a character that describes a person who always accompanies and entertains his employer. However, in this day and age, the function of gagging has become very significant because it is so coveted and becomes a dish that is so intriguing for the audience. This is very much in line with the function of panakawan in general, namely as a medium for educators, lighters, and entertainers. Panakawan figures are also often used as a medium for expressing the soul of the puppeteers who play them, because jokes will continue to develop and in different ways in each place or region. As for the theory used in writing this time, namely the theory of humor from Thornos and Powell (1993) using a qualitative approach, literacy sources used include interviews, literature study, and observation. The case study carried out is the Karawang gagrak which has its own characteristics from time to time, including in the days of R.H Tjetjep Supriadi, Ujang Mukhtar, and Apep As Hudaya, which have a distinction and packaging in their own humor.